Determinants of adolescent pregnancy and their impact on the fundamental axes of income and educational level - Tafur Bonilla, Yenizer Alexandra; Barbosa Campos, Olga Lucia; Méndez Ortiz, Edwin Leonardo (Cooperativismo & Desarrollo, 2018)
Introduction: The present article aims at measuring socioeconomic impact of women’s adolescent pregnancy in key aspects such as income and educational level.Methodology: A survey to Minuto de Dios University students of the Virtual and Distance modality was conducted. The sample comprised 201 surveys and sought to prove the proposed models for determining adolescent pregnancy and also its impacts on educational level and current income. The surveyed women were divided into three categories: adolescent mothers with a current couple, currently single adolescent mothers and women who did not become mothers during adolescence.Results: After analyzing the proposed linear regressions, different axes were found: family group, women’s marital status and their beginning to work in relation to adolescent pregnancy.Conclusions: It was found that the axes studied impact in adolescence and in the current life of any woman from her adolescence to the present.
Keywords: adolescent pregnancy; impacts; income; educational level; endogenous variable